IMPROVING THE STUDENT’S COMPETENT KNOWLEDGE OF INDEPENDENT TEACHING ASSIGNMENTS IN TEACHING RUSSIAN RELEVANCE - Adolat Eshonqulova Neymatovna (Galaxy International Interdisciplinary Research Journal, 2023)
Independent work is not an end in itself. This is a means of fighting for students to obtain deep and lasting knowledge, the formation of their activity and independence as personal qualities, the development of intellectual abilities. A child who has crossed the threshold of an educational institution for the first time cannot independently determine the purpose of his activity, plan his actions, adjust their implementation and link the result with the goal. In the process of learning in the classroom, he must achieve a certain high level of independence, which opens up the possibility of learning in the process of solving various problems, solving educational problems.